Pengaruh Konsep Diri Terhadap Tingkat Kepercayaan Diri Pada Mahasiswa - Syifa Asha Umarta; Wustari. L. Mangundjaya (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to determine whether there is an influence between self-concept and the level of self-confidence in student at University X in Bekasi, as well asÂ the extent of the influence of self-concept on the level of self-confidence . The research method used quantitative research methods involving 263 students, using convenience sampling. Data was collected using two questionnaires, namely self- concept and and selef-confidence, which was tested its reliability and validity.Â Data was processed using simple linear regression. The results showed that self concept had influenced 76,8% to seld-confidence.